Report on Various Diagnostic Methods for Breast Cancer Detection in Women - A. Amir Anton Jone, T. Anita Jones Mary Puspha, Navin M George, P. Esther Jebarani, K. Martin Sagayam, Suresh Subramanian (International Journal of Advanced Science and Technology, 2020)
Breast cancer is dreadful and life threatening disease. The causative agent of breast cancer is still under research. Breast cancer affects one in eight women. The statistics shows that 6 percent of women in India die due to breast cancer. Breast cancer is the second important cause of death. Generally breast cancer is a malignant tumor that begins in the cells of the breast and eventually it spreads to the surrounding tissues. The disease can be treated if it is detected early. As stages increases, the chance of curing decreases. There are various imaging techniques that play a vital role in detecting breast cancer. This survey is an attempt to showcase various breast cancer detection techniques based on image processing technique and an overview about the advantages and disadvantages of each technique is provided. Plenty of work has been done in this field in order to cure this deadliest disease. The medical imaging has revolutionized the field in detecting cancer. Here by a survey of various techniques that can detect cancer is presented.